2021
DOI: 10.1074/jbc.ra120.015059
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 acts upstream of TRPV4 to induce pathological changes in endothelial cells due to shear stress

Abstract: The ion channels Piezo1 and TRPV4 have both, independently, been implicated in high venous pressure– and fluid shear stress–induced vascular hyperpermeability in endothelial cells. However, the mechanism by which Piezo1 and TRPV4 channels execute the same function is poorly understood. Here we demonstrate that Piezo1 regulates TRPV4 channel activation in endothelial cells and that Piezo1-mediated TRPV4 channel opening is a function of the strength and duration of fluid shear stress. We first confirmed that eit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 72 publications
3
89
0
1
Order By: Relevance
“…Other early responses led to mechanically gated channels such as transient receptor potential cation channel V4 (TRPV4) and Piezo1. These are sensitive to changes in the endothelial cell membrane’s tension resulting from fluid shear stress [ 109 ].…”
Section: The Effect Of Hemodynamics On Smooth Muscle Cell Phenotype During Arteriogenesismentioning
confidence: 99%
“…Other early responses led to mechanically gated channels such as transient receptor potential cation channel V4 (TRPV4) and Piezo1. These are sensitive to changes in the endothelial cell membrane’s tension resulting from fluid shear stress [ 109 ].…”
Section: The Effect Of Hemodynamics On Smooth Muscle Cell Phenotype During Arteriogenesismentioning
confidence: 99%
“…Recently shear stresses at physiological (≤ 5 dyne/cm 2 ) and pathological levels were used to determine the amount and duration of shear stress forces that influenced [Ca 2+ ] i in HUVECs. A force of 12 dyne/cm 2 applied for 1 min resulted in a sustained increase in [Ca 2+ ] i , while the same force applied for 1 or 5 s, or lower shear stress (4 dyne/cm 2 ) for 1 min was not enough to induce a sustained increase in [Ca 2+ ] i and resulted in just a transient increase 70 .…”
Section: Resultsmentioning
confidence: 94%
“…TRPV4 and Piezo1 are non-selective calcium-permeable ion channels that can be activated by mechanical stimuli such as compression, hydrostatic pressure, or fluid flow (i.e., shear stress). TRPV4 is thought to operate as a signal transducer that responds to shear stress [68][69][70][71][72] . Shear stress regulates intracellular calcium [Ca 2+ ] i in endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these effects may be due to TRPV4 acting downstream of other mechanosensitive channels, such as Piezo1 (see Section 3) [77,172]. For example, Swain and colleagues reported that Piezo1 and TRPV4 act in concert to initiate and sustain Ca 2+ influx in response to mechanical stimulation in human pancreatic acinar cells [77] and in response to shear fluid stress in human EC [172], with activation of Piezo1 prompting TRPV4 activity.…”
Section: Trpv4mentioning
confidence: 99%
“…Some of these effects may be due to TRPV4 acting downstream of other mechanosensitive channels, such as Piezo1 (see Section 3) [77,172]. For example, Swain and colleagues reported that Piezo1 and TRPV4 act in concert to initiate and sustain Ca 2+ influx in response to mechanical stimulation in human pancreatic acinar cells [77] and in response to shear fluid stress in human EC [172], with activation of Piezo1 prompting TRPV4 activity. TRPV4 knockdown also diminished Piezo1 sensitivity to Piezo1-specific agonists [77], thus indicating that the channels may act in concert to confer mechanical signalling, with Piezo1 acting as the mechanical force sensor [77,172].…”
Section: Trpv4mentioning
confidence: 99%